2017
DOI: 10.1016/j.virol.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and pathological consequences of coxsackievirus RNA persistence in the heart

Abstract: Type B coxsackieviruses (CVB) can cause myocarditis and dilated cardiomyopathy (DCM), a potentially-fatal sequela that has been correlated to the persistence of viral RNA. Herein, we demonstrate that cardiac RNA persistence can be established even after an inapparent primary infection. Using an inducible Cre/lox mouse model, we ask: (i) Does persistent CVB3 RNA cause ongoing immune activation? (ii) If T1IFN signaling into cardiomyocytes is ablated after RNA persistence is established, is there any change in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It may well be that, along time, calpains have become an important backup system in polyprotein processing, while the viral proteases have promoted the infection also by other means, such as cleaving host cell factors related to apoptosis, immune responses, and cellular translation [10]. It has been shown that enteroviruses may stay silent or persistent in tissues for long periods without causing much damage or cell death [3,56,57]. In such circumstances, the viral proteases are likely to be downregulated not to promote apoptosis and cell death, while calpains may still help the polyprotein to be processed further.…”
Section: Discussionmentioning
confidence: 99%
“…It may well be that, along time, calpains have become an important backup system in polyprotein processing, while the viral proteases have promoted the infection also by other means, such as cleaving host cell factors related to apoptosis, immune responses, and cellular translation [10]. It has been shown that enteroviruses may stay silent or persistent in tissues for long periods without causing much damage or cell death [3,56,57]. In such circumstances, the viral proteases are likely to be downregulated not to promote apoptosis and cell death, while calpains may still help the polyprotein to be processed further.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is considerable evidence for a protective contribution of such an immune reaction, there is also consensus that the inflammatory process triggered by virus infection of heart tissue actually drives cardiac damage responses, leading to disarranged cardiac cells, fibrotic tissue repair and ventricular dilation [ 14 ]. It was once thought that the presence or the persistence of virus genomes in the human heart determines disease outcome in viral myocarditis, but that idea has since been discarded [ 19 ]. In fact, the abundance of infiltrating leukocytes is an independent risk factor for the pathologic progression of acute myocarditis into long-term cardiac dysfunction [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical presentations can be mild (flu‐like or febrile symptoms, hand, foot and mouth disease 1 ) or severe (meningitis, 2 acute flaccid paralysis, 3 pancreatitis, 4 acute myocarditis, and pericarditis 5,6 ). CVB seem also able to establish persistent infection in heart 7 and pancreatic islets, 8 and the reactivation could be linked to disease development 6 . Interestingly, CVB infection has been proposed as immunologic trigger for the development of insulin‐dependent diabetes, 9,10 although currently there are no confirmed causal evidence.…”
Section: Introductionmentioning
confidence: 99%